Pro-Environmental Behaviours among Frontliner Employees in Oil and Gas Industry: Does Environmental Work Culture Really Matters? - Amin, Izzat; Zailani, Suhaiza; Rahman, Muhammad Khalilur (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. This study investigates the employee perceptions of organizational environmental initiatives and their impact on pro-pro-environmental behaviors and frequency of involvement in upstream oil and gas companies in Malaysia, such as the Production Arrangement Contractor and Service Provider Company. The study also examines a new area where environmental work culture acts as a moderator. Analyzed using SmartPLS, our findings demonstrate that supervisory support for environmental initiatives and environmental training has a positive effect on employee perception of organizational support for pro-pro-environmental behaviors. In contrast, the organization's rewards for pro-environmental behaviors do not have a significant impact on it. Following this, the employees' perceptions of organizational support for pro-environmental behaviors positively affect employee engagement in pro-environmental behaviors in both forms of employees' frequency of involvement and employees' innovative pro-environmental behaviors. The findings discovered that environmental work culture moderates the relationship of the effect of the organization's support practices on employee perception of organizational support for pro-environmental behaviors. This study is one of the first attempts to investigate the relationship between the pro-environmental behaviors within the upstream firms in the oil and gas industry. The findings are useful for practitioners in terms of exerting pro-environmental behaviors and facilitating employees' pro-environmental behaviors in the upstream oil and gas management sector.      Keywords:  Employee perceptions, pro-environmental behaviors, organizational support, work culture